Measurement of gas-plasma torch temperature - Klepikov, V.F.; Shchelokovskyy, P.A.; Kryshtal, P.G.; Tolstolutskiy, A.G.; Uvarov, V.V. (Вопросы атомной науки и техники, 2001)
Experimental studies of gas-plasma torch optical spectra were performed and the torch temperature on different distances from the target irradiated by high-current REB was measured.